2022
DOI: 10.1177/02610183221137818
|View full text |Cite
|
Sign up to set email alerts
|

Young people's schooling trajectories and transitions to social adulthood in the context of Brazil's Bolsa Família

Abstract: As cash transfers have become key tenets of social protection systems in the global South, much effort has gone into evaluating their outcomes. Less attention has been paid, however, to young beneficiaries’ experiences of cash transfers and the contextualised and differentiated impacts on their lives at the micro-level. Based on a qualitative study of young recipients of Brazil's Bolsa Família programme, this article explores the factors that shape young people's schooling trajectories. The article demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…It has been reported elsewhere in the literature that the aspirations of CCT programme recipients can be exceedingly high and lead to tensions between expected and realised outcomes (Jones, 2019). This study did not appear to present similar findings with many seeing education and Prospera in general as the best way for their children to break the intergenerational cycle of poverty, which is a key element in the programme too.…”
Section: Long-term Aspirations Of Recipientscontrasting
confidence: 67%
See 2 more Smart Citations
“…It has been reported elsewhere in the literature that the aspirations of CCT programme recipients can be exceedingly high and lead to tensions between expected and realised outcomes (Jones, 2019). This study did not appear to present similar findings with many seeing education and Prospera in general as the best way for their children to break the intergenerational cycle of poverty, which is a key element in the programme too.…”
Section: Long-term Aspirations Of Recipientscontrasting
confidence: 67%
“…The repetitive aspiration to 'be somebody' with a degree of significance in society and self-worth is regularly evoked with a desire to achieve a white collar position such as 'manager' or 'professional' (Jones, 2019). An aspiration to attain careers in traditionally white collar employment is consistent in the literature among young people living in poverty (Jeffrey et al, 2004;Crivello, 2011).…”
Section: Long-term Aspirations Of Recipientsmentioning
confidence: 71%
See 1 more Smart Citation
“…Some have suggested that the concept of transitions creates false binaries, for example, between education and work, or youth and adults. Alternatives aim to be more in line with the nonlinear reality of youth, such as "critical moments" or "vital conjectures" (Jones 2022). In this report, the concept of transitions is considered instructive and valuable when understood in terms of the complexity, multiplicity, and nonlinear nature of young people's trajectories into, back into, and within the labor market.…”
Section: Employment Transitions Of a Youth Cohort In Australia 2000-2010mentioning
confidence: 99%
“…3.2.1 Análisis conceptual sobre los programas de transferencia monetaria Los programas de PTM se inscriben dentro del amplio campo de los sistemas de protección social, así como de las políticas sociales y se han convertido en una pieza clave en el sur global (Jones, 2022). Consisten en la entrega de recursos monetarios y no monetarios a ciertos grupos en situación de vulnerabilidad y pobreza como: familias con hijos menores de edad, adultos mayores, personas con discapacidad, y otros grupos, establecidos de acuerdo con los lineamientos institucionales de cada país.…”
Section: Programas De Transferencia Monetaria (Ptm)unclassified